The level of acceptance in adopting the philosophy of market orientation in the Malaysian public organizations / Nurulaini Zamhury, Rugayah Hashim and Jasmine Ahmad - Zamhury, Nurulaini; Hashim, Rugayah; Ahmad, Jasmine (Universiti Teknologi MARA, Shah Alam, 2010)
A major feature of the new public management (NPM) concept is its market-oriented approach. The premise of NPM reform wave is that more market orientation in the public sector will lead to greater cost-efficiency for government, without having negative side effects on other objectives and considerations. It is hypothesized that the presence of those four independent variables will influence public employees to exhibit market-oriented values. Therefore, the objective of this study is to examine the influence of organizational leadership, professional attitudes, entrepreneurial values, and macro-environment context within the parameters of the new public management (NPM). Survey questionnaires were sent out to 248 public officials in four federal government agencies in the capital city of Shah Alam, Selangor, Malaysia. The response rate was 60.5%. The findings indicated that only professional attitudes and macro-environment context are statistically significant while organizational leadership and entrepreneurial values were positively related to market orientation but were statistically insignificant.